Oxygen delivery-utilization matching in skeletal muscle - Hirai, Daniel Muller (Kansas State University, 2012)
The overall aim of this dissertation is to better understand the mechanisms determining skeletal muscle oxygen delivery-utilization matching in health and disease. Emphasis is directed toward the role of nitric oxide (NO) bioavailability in modulating muscle microvascular oxygenation (PO2mv; the sole driving force for blood-myocyte oxygen flux) during transitions in metabolic demand. The first investigation of this dissertation (Chapter 2) demonstrates that alterations in NO bioavailability have a major impact on skeletal muscle PO2mv kinetics following both the onset and cessation of contractions. Specifically, increased NO levels (via the NO donor sodium nitroprusside; SNP) elevates whereas reduced NO levels (non-specific NOS inhibition with NG-nitro-L-arginine methyl ester; L-NAME) diminishes muscle PO2mv at the onset and during recovery from contractions in the spinotrapezius muscle of healthy young rats. Consistent with these results, inhibition of the neuronal NO synthase isoform (S-methyl-L-thiocitrulline; SMTC; Chapter 3) reveals alterations in NO-mediated regulation of skeletal muscle PO2mv with advanced age that likely contribute to exercise intolerance in this population. In Chapter 4 we observed that pronounced oxidative stress is implicated in these pathological responses seen in aged and diseased states. Transient elevations in the oxidant hydrogen peroxide to levels seen in the early stages of senescence and cardiovascular diseases promote detrimental effects on skeletal muscle contractile function (i.e., augmented oxygen cost of force production). Chapter 5 demonstrates that endurance exercise training improves skeletal muscle microvascular oxygenation (i.e., greater PO2mv and slower PO2mv kinetics) across the metabolic transient partly via enhanced NO-mediated function in healthy young individuals. These data carry important clinical implications given that exercise training may ameliorate NO-mediated function, muscle microvascular oxygenation deficits and consequently exercise intolerance in aged and diseased populations. In conclusion, alterations in NO bioavailability have a major impact on the dynamic balance between skeletal muscle oxygen delivery and utilization (i.e., PO2mv kinetics) in health and disease. While advanced age or the predations of disease impair considerably skeletal muscle microvascular oxygenation, exercise training-induced adaptations on the oxygen transport system constitute a non-pharmacological therapeutic intervention potentially capable of mitigating these microcirculatory deficits.
Keywords: Exercise; Physiology; Nitric oxide; Microcirculation; Biology, Animal Physiology (0433); Health Sciences (0566); Physiology (0719)